2021
DOI: 10.1021/acs.macromol.1c01055
|View full text |Cite
|
Sign up to set email alerts
|

N–B ← N Bridged Bithiophene: A Building Block with Reduced Band Gap to Design n-Type Conjugated Polymers

Abstract: The development of conjugated polymers with excellent performance of optoelectronic device depends to a large extent on the molecular design of electron-accepting (A) building blocks. Previously reported A building blocks based on a bithiophene skeleton always show lower lowest unoccupied molecular orbital (LUMO) and highest occupied molecular orbital (HOMO) energies compared to those of bithiophene itself. Herein, we report a new A building block (BNTzT), in which the thiophene−thiazole skeleton is bridged by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 97 publications
0
12
0
Order By: Relevance
“…In addition, the electron transfer process of the electron-rich Eu-MOF to electron-deficient NAEs is another reason for fluorescence quenching. When the analyte has a lower LUMO energy level, it is easier to receive electrons from the LUMO energy level of the fluorescent substance, 47 resulting in fluorescence quenching. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the electron transfer process of the electron-rich Eu-MOF to electron-deficient NAEs is another reason for fluorescence quenching. When the analyte has a lower LUMO energy level, it is easier to receive electrons from the LUMO energy level of the fluorescent substance, 47 resulting in fluorescence quenching. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Since the discovery of the ability of conjugated polymeric backbones to transport holes and electrons in electronic devices, these polymers have been extensively studied and used in optoelectronic applications such as organic solar cells (OSCs), organic electronic devices, organic transistors, and organic photodetectors (OPDs). To enhance the charge transport characteristics, most conjugated polymers have been designed and synthesized to allow strong π-conjugation and π–π stacking interactions in polymeric chains. To date, several synthetic strategies are being implemented to increase the π-conjugation length of polymeric chains. Recently, interest in photodiodes, which convert light to electrical signals or energy, has increased substantially; n-type polymers capable of promoting this conversion are being actively developed. Owing to the electron-sufficient nature of conjugated polymers, numerous strong electron-withdrawing units such as nitriles and imides are incorporated in the conjugated backbones, and large fused aromatic rings are often utilized to enhance the electron transport properties of n-type polymers. Fan et al reported a 2,2′-((2 Z ,2′ Z )-((4,4,9,9-tetrahexyl-4,9-dihydro- s -indaceno­[1,2- b :5,6- b ′]­dithiophene-2,7-diyl)­bis­(methanylylidene))­bis­(3-oxo-2,3-dihydro-1 H -indene-2,1-diylidene))­dimalononitrile (IDIC)-based n-type polymer, which exhibited a high power conversion efficiency (PCE) of 10.8% in OSCs . Further PCE enhancement was achieved by using a 2,2′-((2 Z ,2′ Z )-((12,13-bis­(2-ethylhexyl)-3,9-diundecyl-12,13-dihydro-[1,2,5]­thiadiazolo­[3,4- e ]­thieno­[2″,3″:4′,5′]­thieno­[2′,3′:4,5]­pyrrolo­[3,2- g ]­thieno­[2′,3′:4,5]­thieno­[3,2- b ]­indole-2,10-diyl)­bis­(methanylylidene))­bis­(5,6-difluoro-3-oxo-2,3-dihydro-1 H -indene-2,1-diylidene))­dimalononitrile (Y6) moiety.…”
Section: Introductionmentioning
confidence: 99%
“…Organoboron chemistry offers an important toolbox to design conjugated polymers with tunable opto-electronic properties. 22,23 For example, Helten et al have reported a boron–nitrogen analogue, poly( p -phenylene vinylene) (PPV), and provided clear evidence for π-conjugation across the BN units along the polymer backbone. 24 Jäkle and co-workers have confirmed that B–N functionalized ladder-type dipyridylfluorene monomers could be used as building blocks for the preparation of luminescent conjugated polymers with tunable emission characteristics.…”
Section: Introductionmentioning
confidence: 99%